A review of the fantaserye Encantadia based on a feminist perspective. - Enriquez, Irene Grace M.; Flores, Darcy clarito V.; Pagulong, Charmie Joy B.; Sernicula, Loudielyn N. (2005.)
Generally, this study aims to find out whether Encantadia is a media text wherein the ideas of feminist theories are manifested. The study will provide information and a deeper understanding of women's role as portrayed in the contemporary television programs more specifically in the fantaserye Encantadia., The respondents chosen are avid enthusiast of the fantaserye Encantadia. They vary from college students, Young professionals, to professionals. The study showed that Encantadia is a media text which advocates to the goal of feminist theories. Gender equality is achieved as explained and supported by the Social Relations Framework, Levels of Equality Framework, Ecofeminism and Psychoanalytic Feminism.
Thesis (Undergraduate, Bachelor of Arts in Broadcast Communication) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Encatadya, Fantaserye -- Feminist Perspectives